Handbook for digital signal processing - Mitra, Sanjit Kumar; Kaiser, James F. (John Wiley & Sons, 1993)
Discusses important topics in modern digital signal processing. Designed to fill the needs of practicing engineers and designers of hardware systems and software. The editors present the principal applications of the subject, followed by coverage of such topics as linear time-invariant discrete-time systems, finite- and infinite- impulse response digital filter design, digital filter implementation considerations, signal conditioning and interface circuits, hardware and architecture, multirate signal processing, and adaptive filtering.